Psychiatric mental health nurse practitioner outcomes after completion of a 1-year postgraduate fellowship - Anna Pasternak; Hilary Gould; Alexandra Sietsma; Crystal Ross; Steve Koh (Journal of the American Association of Nurse Practitioners, 2026)
ABSTRACT Psychiatric mental health nurse practitioners (PMHNPs) are an essential and growing part of the health care workforce, especially in community settings. To address PMHNPs' increasing presence in community psychiatry, a 1-year postgraduate PMHNP fellowship in community psychiatry was developed with the goals of enhancing clinical competency and employment retention in underserved public sector settings. Data on 5 cohorts and 31 fellows are presented in this article. PMHNP fellows, preceptors, didactics, and clinical sites were evaluated across several time points including baseline and 6 and 12 months. The program has graduated 100% of fellows with largely positive feedback. Fellows reported significant improvements in competency across the domains of 1) assessment and diagnosis, 2) treatment, and 3) professionalism and leadership. These items were substantiated by clinical preceptors' ratings of fellows' clinical skills from 6-month and 12-month time points. Relatedly, clinical sites, preceptors, and didactics were all rated highly by fellows. After the program, 90.3% of graduates remained working in the public sector including correctional settings, community clinics, and safety net hospitals.